Analisis Kepuasan Pelayanan Aplikasi Maxim pada Pengguna Mahasiswa Institut Agama Islam (IAI) Diniyyah Pekanbaru - Irwandi, Irwandi; MZ, Nurse Fatimah (AL-Muqayyad, 2023)
The title of this study is "Analysis of Maxim Application Service Satisfaction on Users of Islamic Religious Institute (IAI) Diniyyah Pekanbaru Students". The purpose of this study is motivated by the author's observations to determine the extent of customer satisfaction with the maxim application. In order to collect, compile and process the data in this study, the authors used field research methods (field research). Based on the results of the research that the authors have done, it can be concluded that the Maxim Application Service Satisfaction Analysis for Islamic Religious Institute (IAI) Diniyyah Pekanbaru Student Users is good and quite developed. Meanwhile, the Islamic Economics review of the Maxim Application Service Satisfaction analysis for Diniyyah Pekanbaru Islamic Institute (IAI) Student Users has not applied Islamic sharia principles, because the system sometimes harms both drivers and customers.